SURVEY, MEDIA REQUIREMENT AND MANAGEMENT OF FUSARIUM WILT OF PEA - MOHD ALI; SACHIN KUMAR JAIN; MEHI LAL; MOHAMMAD ZUHAIB; SANTOSH KUMAR; ANAND SWAROOP SRIVASTVA (The Bioscan, 2014)
Fusarium wilt caused by Fusarium oxysporum Schl. f. sp. pisi Snyd & Hans, is a fungal disease that affects peas and is important worldwide. A survey was carried out for assessing the disease outbreak in pea growing areas of 10 blocks of district Kanpur Nagar in Uttar Pradesh. The highest average percentage of wilt incidences was recorded in Bhitargaon block (15%) while minimum percentage was recorded in Sarsol block (9%). Out of seven solid and liquid media, potato dextrose agar medium/potato dextrose medium was found best and supported maximum fungal growth (7.70 cm) and maximum dry mycelial weight (440.18 mg). Same composition of media was also found best for sporulation. Eight bioagents were evaluated against Fusarium oxysporum f. sp. pisi and showed varying degrees of antagonism. Maximum inhibition percentage was observed with Aspergillus niger (62.77%) and lowest was with Chaetomium globosum (39.70%). Out of 23 accessions none was found immune/ resistant and 15 were moderately resistant, 2 were moderately susceptible, 3 accessions were found susceptible and remaining were found highly susceptible. Present study reported suitable media for growth and sporulation of Fusarium oxysporum f.sp. pisi and two management strategies viz., bioagents and resistant sources. Both management strategies could be used for integrated management of this disease in eco-friendly way.